Empat Model Hubungan Agama dan Sains Menurut John. F. Hought - Nurul Muttaqin (Tarbawi: Journal of Islamic Education, 2021)
The intersection and the relationship between the two are often found in ambiguous and contradictory, complicated dichotomies and difficulty finding common ground have made many people try to make arguments that strengthen, that religion and science need to be brought together in logical mediation, whyu-based theological references and brain-based science and experiments often clash head-on in scrambling for followers. Pendektan JF. Hock to reconcile the two came to a four-step positional conclusion, which aims to direct religion to the path it wants and not carry out science to submit to its will. Science questions that often touch religion with; does science want to get rid of the transcendent existence of God? This analysis yields interesting things, and it can raise questions directly about the alignment of science with the religions of God and raise awareness, but perhaps there is a paradox here when we feel very comfortable with our theistic religion, so that this makes us not interested in this, let alone trying to connect with science, or perhaps our tendency to reject ourselves actually makes something that alienates us from religion, but academic education makes it impossible for us to leave this conversation, let alone see the possibility of talking about God and the definitions of nature allows theology to reform the concept of mind of its adherents. The discourse on the integration of science and religion has been long enough, F. Haught, emphasized to respect religion which can support science to make it meaningful, so that religion can play an important role in the development of science. Likewise science can enrich and renew theological understanding. John F. Haught, divides the approach of science and religion into four approaches; First, the conflict approach. Second, the contrasting approach, third, the contact approach, and fourth, the confirmation approach. These four views can be seen as a kind of typology and seen as a kind of journey.